Facile deposition of Ag3PO4 nanoparticles on Bi2MoO6 nanoplates by microwave for highly efficient photocatalysis - Phonthep Nualkaew (2018)
© 2017, Pleiades Publishing, Ltd. A simple microwave method has been successfully developed to effectively produce Ag 3 PO 4 /Bi 2 MoO 6 nanocomposites. X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) have been employed to determine the phase and morphology of the as-produced products. The photocatalytic activities were tested through the rhodamine B (RhB) degradation under visiblelight radiation. The interaction between cubic Ag 3 PO 4 nanoparticles and orthorhombic Bi 2 MoO 6 nanoplates has been characterized by XRD and TEM. In this research, the as-produced heterostructure Ag 3 PO 4 /Bi 2 MoO 6 nanocomposites display effective photogenerated charge transfer between Ag 3 PO 4 and Bi 2 MoO 6 which can improve charge separation. The 10.0 wt % Ag 3 PO 4 /Bi 2 MoO 6 nanocomposites showed the highest photocatalytic performance as high as 4.36 times of the pure Bi 2 MoO 6 sample.